A Latent Class Approach to Understanding Associations between Sports Participation, Substance Use, Dismissive Attitudes, and Sexual Violence Perpetration among High School Athletes. Issue 13 (July 2022) - Ingram, Katherine M.; Basile, Kathleen C.; Leemis, Ruth; Espelage, Dorothy L.; Valido, Alberto
Sexual violence (SV) among adolescents continues to be a major public health concern with numerous consequences. Research, predominantly with male collegiate samples, has suggested an association between sports participation and SV perpetration, and has included other important risk factors such as substance use and attitudes. However, more research is needed in this area among adolescents. The current study uses latent class analysis (LCA) to examine data- driven classes of high school student athletes (N = 665) engaged in three risk factor areas for SV: sport contact level, likelihood of substance use, and attitudes dismissive of SV. Once classes were enumerated and fit separately for male and female samples, pairwise comparisons were conducted on scores on two forms of SV (perpetration of sexual harassment and unwanted sexual contact) as a function of class membership. A 5-class solution was retained for both males and females. In the female sample, regarding SV—harassment, those most likely to perpetrate sexual harassment were those characterized by high likelihood of use of cigarettes, marijuana, alcohol, vape products, and those who played any type of sport. Too few females endorsed perpetration of unwanted sexual contact for pairwise comparisons to be conducted. For males, the classes most likely to perpetrate both forms of SV were those who were likely to endorse high likelihood to use of cigarettes, marijuana, alcohol, vape products, endorse attitudes dismissive of SV, and play any type of sport but especially high contact sports. These findings implicate high school athletic spaces as important venues for sexual violence prevention efforts.